Traffic light regulating system simulation at Surakarta city using decision table - Heribertus Ary Setyadi; Yusuf Sutanto (Institute of Computer Science (IOCS), 2023)
The effectiveness of a transportation system depends on its ability to support the reliable movement of people, goods, and vehicles from one place to another. An urban traffic system is an important yet complex transportation system composed of vehicles, pedestrians, traffic lights, and a traffic network structure. Existing traffic lights are usually configured with a fixed cycle, and do not take into account specific traffic conditions. Such a configuration is very inefficient. When a large event is held during rush hours, it inevitably gives rise to traffic congestions. The purpose of this research is to produce a system for simulating traffic lights base on predetermined four criterias in order to reduce coongestion. The four criterias are intersections amount, vehicle density in a certain period of time, road width and one way street. Output of this system are engineering simulation and traffic light regulation at the intersection. The problem discussed and worked on in this research is set the time of traffic lights or the time of the red lights and green lights which are at the three intersection and four intersection. The analysis phase is to analyze the process at Surakarta Transportation and Information Agency in traffic lights. The next step is to analyze the weaknesses of the system and analyze the needs of the system being developed. The developed system can produce traffic light simulations and traffic engineering at intersections that includes setting the time the lights are red and green, the green lights are on at the same time and the rules for turn left may go.